Apakah Kartu Indonesia Pintar Kuliah (KIP-K) Efektif sebagai Instrumen Pembangunan untuk Meningkatkan Akses Pendidikan Tinggi? - Wisdawati, Ramadhana Aulia; Hanafi, Muhammad (Akuntansi & Ekonomika, 2025)
The Indonesia Smart Card (KIP) plays an important role in supporting the government's efforts to expand access to education for students from low-income families. This study aims to evaluate the role of KIPK and other factors in promoting higher education participation in Indonesia. The data used were obtained from the 2022 National Socio-Economic Survey (Susenas). The analysis was conducted using logistic regression to identify the influence of various variables on higher education participation. The results show that ownership of KIPK and assistance from the Family Hope Program (PKH) significantly contribute to increasing higher education participation. These findings highlight the importance of social assistance programs in promoting access to higher education for vulnerable groups